Efficient Plasmonic Au/CdSe Nanodumbbell for Photoelectrochemical Hydrogen Generation beyond Visible Region. Issue 15 (25th February 2019) - Wang, Hongzhi; Gao, Yuying; Liu, Jia; Li, Xinyuan; Ji, Muwei; Zhang, Erhuan; Cheng, Xiaoyan; Xu, Meng; Liu, Jiajia; Rong, Hongpan; Chen, Wenxing; Fan, Fengtao; et al.
Abstract: In this communication, light harvesting and photoelectrochemical (PEC) hydrogen generation beyond the visible region are realized by an anisotropic plasmonic metal/semiconductor hybrid photocatalyst with precise control of their topology and heterointerface. Controlling the intended configuration of the photocatalytic semiconductor to anisotropic Au nanorods' plasmonic hot spots, through a water phase cation exchange strategy, the site‐selective overgrowth of a CdSe shell evolving from a core/shell to a nanodumbbell is realized successfully. Using this strategy, tip‐preferred efficient photoinduced electron/hole separation and plasmon enhancement can be realized. Thus, the PEC hydrogen generation activity of the Au/CdSe nanodumbbell is 45.29 µmol cm −2 h −1 (nearly 4 times than the core/shell structure) beyond vis (λ > 700 nm) illumination and exhibits a high faradic efficiency of 96% and excellent stability with a constant photocurrent for 5 days. Using surface photovoltage microscopy, it is further demonstrated that the efficient plasmonic hot charge spatial separation, which hot electrons can inject into CdSe semiconductors, leads to excellent performance in the Au/CdSe nanodumbbell. Abstract : In this communication, light harvesting and photoelectrochemical hydrogen generation beyond the visible region are realized by an anisotropic plasmonic metal/semiconductor hybrid photocatalyst with precise control of its topology and heterointerface.